2000
DOI: 10.1126/science.288.5467.870
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of JNK for Stress- Induced Activation of the Cytochrome c-Mediated Death Pathway

Abstract: The c-Jun NH2-terminal kinase (JNK) is activated when cells are exposed to ultraviolet (UV) radiation. However, the functional consequence of JNK activation in UV-irradiated cells has not been established. It is shown here that JNK is required for UV-induced apoptosis in primary murine embryonic fibroblasts. Fibroblasts with simultaneous targeted disruptions of all the functional Jnk genes were protected against UV-stimulated apoptosis. The absence of JNK caused a defect in the mitochondrial death signaling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

99
1,305
12
11

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,584 publications
(1,433 citation statements)
references
References 44 publications
99
1,305
12
11
Order By: Relevance
“…Further support arose from data obtained using dominant-negative c-Jun mutants, which reduced sympathetic neuronal death following NGF withdrawal [214]. A pro-apoptotic function has also been suggested for JNK activation in NGFwithdrawal-induced neuronal death [59] in a hippocampal model of Huntington's disease [124] and in beta-amyloidinduced neuronal apoptosis [204]. However, the apoptotic process does not occur in JNK-knockout mice [222] or mice expressing a mutant form of c-Jun lacking the JNK phosphorylation site [15].…”
Section: Map Kinase Signalingmentioning
confidence: 96%
See 3 more Smart Citations
“…Further support arose from data obtained using dominant-negative c-Jun mutants, which reduced sympathetic neuronal death following NGF withdrawal [214]. A pro-apoptotic function has also been suggested for JNK activation in NGFwithdrawal-induced neuronal death [59] in a hippocampal model of Huntington's disease [124] and in beta-amyloidinduced neuronal apoptosis [204]. However, the apoptotic process does not occur in JNK-knockout mice [222] or mice expressing a mutant form of c-Jun lacking the JNK phosphorylation site [15].…”
Section: Map Kinase Signalingmentioning
confidence: 96%
“…This malfunction is significant since it is critical for the subsequent sequential activation of Apaf-1 [120], the initiator-caspase caspase-9 [76] and finally the effector-caspase caspase-3 [217] all of which are essential in the execution of apoptosis. Tournier et al [204] suggested that the apoptotic response is suppressed in JNK null MEF due to the absence of JNK, which is needed to initiate the apoptotic cascade (Fig. 5).…”
Section: Map Kinase Signalingmentioning
confidence: 97%
See 2 more Smart Citations
“…38 We have previously shown that agonist RRMs induce a strong and sustained activation of stress kinases JNK and p38, which correlates with the induction of apoptosis. 39 JNK is necessary for the release of cytochrome c during stressinduced apoptosis 40 and is known to phosphorylate Bcl-2 and Bcl-X L , hindering their antiapoptotic function. [41][42][43] This contrasts with other studies suggesting that Bcl-2 phosphorylation is required for its antiapoptotic activity.…”
Section: Introductionmentioning
confidence: 99%